Virulência de isolados de Pyricularia oryzae cav. do arroz em poaceas - Ben, Cássio Alberto Vielmo (2019)
Rice is one of the most important cereals grown in Rio Grande do Sul and, being the largest Brazilian producer, has economic and social importance for the State. The blast, caused by the fungus Pyricularia oryzae, is among the main factors limiting the productivity of this crop, which can cause total loss of the crop. This disease affects several crops, but little is known about the sources of virulent inoculum of this disease to rice. Thus, in order to know more about the rice-blast method, the objective of this work was to study the interaction of pathogenicity between isolates and species and the infection of the isolates obtained from these species after inoculation. For this, two experiments were performed. In the first, in a greenhouse, 15 hosts were inoculated with two isolates of this pathogen, one from Tocantins (Isolated 1) and another from Rio Grande do Sul (Isolated 2). At 2, 5, 7, 14, 18, 21 and 28 days disease severity was assessed and classified as susceptible or resistant according to IRRI scale (2013). The number and length of lesions were also evaluated. A completely randomized design was used, with five replications, in factorial scheme 15 x 2, with factor A = hosts and factor B = isolates. Samples of injured leaf tissue were collected and used for experiment 2, where the pathogen was reisolated and identified according to the host and isolated from the source, and after reinoculation on new hosts and the incidence of the disease was evaluated, proving the viable hosts. As a result of the first experiment, five hosts were susceptible to Isolate 1, being the rice cultivars 'IRGA 424', 'IRGA 424 IR', 'IRGA 425', ryegrass and wheat, and six for Isolate 2 being IRGA 424 ',' IRGA 425 ',' Guri INTA CL ',' Puita INTA CL ', ryegrass and wheat. Also, the highest number of lesions was obtained for the cultivar 'IRGA 424 RI' for isolate 1 and 'Guri INTA CL' cultivar for isolate 2. Regarding the lesion size variable, the highest values were found in ryegrass inoculated with Isolate 1 and in the 'Guri INTA Cl' cultivar with Isolate 2. In the second experiment, except for the isolate obtained from wheat plants, all the others were virulent for the Oryza sativa species. These results demonstrated that the wheat crop does not appear to be a host of virulent P. oryzae to rice. On the other hand, they are worried because the isolates obtained from ryegrass and black oat plants have been highly virulent for rice cultivars, because in RS, both species are widely cultivated in inter-harvest periods, in the form of pastures and straw formation and demonstrated to be great hosts for the pathogen.